Módulo de generación de reportes gráficos - Cayetano, Denisse (2009)
Nowadays, computer networks connected to the Internet continue to be compromised and exploited by hackers. This is in spite of the fact that many networks run some type of security mechanism at their connection to the Internet. Large enterprise networks, such as the network for a major university, are very inviting targets to hackers who are looking to exploit them. In the market there are several tools that help the analysis, which could be a possible network attack, but despite of that these tools are available both for free and as owner, they fail in the analysis of large amounts of information (in the order of GBs and TBs). This paper describes a tool for scalable and distributed processing logs of network traffic (pcap format) and the generation of graphical reports from these logs, so that these reports can be used as part of computer forensics processes.